TRADISI MEMBACA AL-QUR'AN: STRATEGI PRE LEARNING DALAM MEMPERSIAPKAN MENTAL SISWA DI MA MATHOLI'UL HUDA TROSO - Firdausiyah, Muhimmatul; As’ad, Ali (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to examine the implementation of reciting the Qur'an before lessons, the mental readiness of students, and the impact of reciting the Qur'an on students' mental readiness at MA Matholi’ul Huda Troso. A qualitative approach was used, with students as the research subjects and the headmaster and teachers as informants. Data was collected through observation, interviews, and documentation. The results of the study indicate that MA Matholi’ul Huda Troso, as a religion-based educational institution, routinely conducts Qur'an recitation activities every morning from 07.15 to 07.30. Before the activity, students perform physical preparation by performing ablution and spiritual preparation to maintain purity and mental readiness. Observations show that this activity helps to calm the students' minds and better prepare them to receive lessons. This activity positively contributes to mental readiness and creates a conducive learning atmosphere.